Diffusion-Weighted MR Imaging of Subdural Empyemas in Children - Wong, Alex M.; Zimmerman, Robert A.; Simon, Erin M.; Pollock, Avrum N.; Bilaniuk, Larissa T. (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Subdural empyema (SDE), an infection of the subdural space, occurs most often in pediatric patients as a complication of meningitis, sinusitis, or otitis media. Diffusion-weighted imaging (DWI) has been used in the past to investigate intracerebral infections. The purpose of this study was to determine the signal intensity characteristics of SDE on DWIs as well as the corresponding apparent diffusion coefficient (ADC) maps.METHODS: MR studies of 10 patients with SDEs were retrospectively reviewed. Included were routine sequences and DWI, which consisted of an axial single-shot echo-planar spin-echo sequence (TR/TE, 4000/110) with b values of 0, 500, and 1000 s/mm2. Signal-intensity characteristics on routine MR images and DWIs were evaluated. In seven patients, ADC values of the lesions were calculated by using two b values. Follow-up imaging study was performed in seven patients.RESULTS: In nine patients, the empyema was hyperintense on DWIs. In the remaining patient, the empyema showed mixed hyperintensity and hypointensity. ADC values were lower than those of normal cortical gray matter and much lower than those of reactive subdural effusions. In all seven patients with persistent clinical signs of infection, the empyemas were hyperintense on follow-up DWIs.CONCLUSION: SDE had high signal intensity on DWIs and low signal intensity on ADC maps, with an ADC value lower than that of the normal cortical gray matter. Diffusion MR imaging can be valuable in distinguishing SDE from effusion and in the follow-up of subdural collections.